Dual career in the workplace: co-creation of a conceptual framework by employers and employee-sportspersons incorporating corporate social responsibility and brand alignment - Fusco, Andrea; MacDonncha, Ciaran; Capranica, Laura; Barat, Chloé; Bichi, Alberto; Blondel, Laurence; Daniel, Rosemary; Doupona, Mojca; Figueiredo, António José; Keldorf, Ole; Mattia, Giovanni; Papale, Olga; et al. (Frontiers in Psychology, 2024)
Introduction The purpose of this study was to provide an evidence base and conceptual framework to inform new guidelines for achieving a balance between sports and employment commitments (i.e., dual career, DC) of the employee-sportspersons. To shape a DC discourse in the workplace, the distinct and combined views of the employee-sportspersons (i.e., the Employee), the managers (i.e., the Employer) were considered. Methods Following a concept mapping methodology, 257 international participants (25% employers and 75% employee-sportspersons) sorted and rated 50 potential statements associated with DC circumstances and supports in the workplace. Results Six distinct clusters emerged, with the combined employers-employee co-creation scenario assigning 6 statements to the micro dimension (Cluster 1 = Workplace Benefits), 4 statements to the meso dimension (Cluster 2 = Role of National Sports Governing Bodies), 19 statements to the macro dimension (Cluster 3 = Dual Career Policy Development), 4 and 5 statements to the organizational dimensions (Cluster 4 = Employee-Employer Collaboration and Responsibility; Cluster 5 = Sport Career Integration), and 12 statements to the policy (Cluster 6 = Workplace Strategies for Dual Career Support) dimension. With respect to the employers, the employee-sportspersons showed higher scores (p < 0.05) for importance of clusters 2, 4, and 6, and for feasibility of clusters 2 and 6. Discussion These findings suggest priorities for changes within the DC dimensions identified, and envisage flexible models for aligning corporate brand values and corporate social responsibility strategies through meaningful and proactive DC support of the employee-sportspersons in the workplace. The findings provide a rigorously derived evidence base to inform the formulation of new DC workplace guidelines.